Komparasi Kepuasan Sistem Pembelajaran Daring Dan Luring Pada Mata Kuliah Kewirausahaan UHN I Gusti Bagus Sugriwa Denpasar - Astrid Krisdayanthi; Ni Made Rai Kristina; Putu Riska Wulandari (Jayapangus Press, 2023)
This research was motivated by changes in the learning situation in universities. During the Covid-19 pandemic, learning was applied with an online system. Towards the middle of 2022, learning has started using offline learning. Online and offline learning, of course, there are differences in atmosphere, such as student interaction with lecturers and fellow students and the need for facilities and infrastructure. This certainly has an impact on student learning satisfaction. This study aims to compare student learning satisfaction in the Entrepreneurship course which is carried out with online and offline learning systems. This research is classified as quantitative research. The population of this study is students of the Faculty of Dharma Duta class of 2021 and 2022. Sampling technique is a saturated sampling technique. The research instrument used is a student learning satisfaction questionnaire that has been tested for validity and reliability. The collected data were analyzed by independent sample T test. The results showed that there was a significant difference in learning satisfaction between students who took the Entrepreneurship course with the online learning model and offline learning. Offline learning provides higher learning satisfaction for students.